Community-based drug checking at syringe service programs in New York City observe an increasing prevalence of xylazine from 2021 through 2024 - Leonardo A. Dominguez Gomez; Yarelix Estrada; Jeffery Sauer; Izza Zaidi; Andrew J. Trinidad; Hannah Helmy; Alex Harocopos (Harm Reduction Journal)
Abstract Background Xylazine has emerged as a major component of the unregulated opioid supply in several jurisdictions across the United States. However, the extent of xylazine in local drug supplies is unknown. Drug checking is a harm reduction strategy that provides information to people who use drugs and allows for insight into the composition of local drug supplies. Methods The New York City Department of Health and Mental Hygiene (DOHMH) worked with syringe service program (SSP) partners to operate a drug checking pilot study that continued as a public health program. Drug samples were submitted by SSP participants for drug checking by trained DOHMH staff and further testing by secondary laboratory partners. The secondary laboratory used both GC/MS and LC-QTOF-MS to identify compounds present in a drug sample. Results Drug samples collected from November 2021 through December 2024 were analyzed. There were N = 1027 secondary laboratory testing results that contained opioids. Of these, n = 449 (43.7%) also contained xylazine. The prevalence of opioids containing xylazine increased from 10.7% in 2021 to 53.7% through 2024. Visualization of the monthly xylazine prevalence, as well as an accompanying chi-square test for trend in proportions (χ2 = 45.229, degrees of freedom = 1, p-value = < 0.001), provided further evidence that the prevalence of xylazine increased over time. Conclusion The prevalence of xylazine in samples containing opioids has increased in New York City from November 2021 through December 2024. Drug checking can monitor changes in the local drug supply and inform existing harm reduction efforts.